Review of Theory of Legal Objectives on Article 31 Section (1) and (2) of Law Number 37 Of 2004 Concerning Bankruptcy and Suspension of Debt Payment Obligations - Bagus Rahman; Ahmad Redi (Publikasiku, 2023)
The bankruptcy case of PT Aliga Internasional Pratama is proof of the dualism of the position of criminal confiscation over general confiscation in the bankruptcy estate. Based on the decision of the Commercial Court at the Central Jakarta District Court, PT. Aliga International Pratama has been legally declared bankrupt with all the legal consequences. Whereas as of the date of the bankruptcy decision, all assets of PT. Aliga is in a state of general confiscation, and the authority to control and manage all of their asset rests with the Curator Team. However, 2 buildings which are bankrupt assets, namely The Aliga Hotel and factory/office buildings, have been confiscated by the Criminal Investigation Police Investigators (Bareskrim Polri).The research method in this paper is descriptive qualitative, namely the legal material obtained is presented descriptively and analyzed qualitatively. The results showed that, analyzed using the theory of justice according to Thomas Aquinas and the theory of expediency by Jeremy Bentham, the provisions of Article 31 paragraphs (1) and (2) of the UUK have fulfilled the values of justice and expediency in their norms. However, analyzed by Jeremy Bentham's theory of legal certainty, the provisions of Article 31 paragraphs (1) and (2) of the UUK do not meet the value of legal certainty. Then the judge's decision has been right and fulfills the elements of certainty, justice, and legal expediency